Comment on "A Broadband Negative Index Metamaterial at Optical Frequencies". Issue 4 (3rd February 2014) - Fietz, Chris
<x xml:space="preserve">Abstract</x> Atre et al. recently presented a design for a new metamaterial which they claimed had two "broadband negative index" bands (Adv. Opt. Mater. 2013, 1, 327). In this comment we show that, when characterized correctly, the metamaterial in question has no such negative index bands. We demonstrate this with two different characterization methods. We also discuss the characterization method which led to the original claim of a negative index material.